A methodological approach to gender analysis in natural disater assesment: a guide for the Carribean - Deare, Fredericka (Serie manuales;31)
The Caribbean region is highly prone to natural disasters, with the increased occurrence in recent years of hurricanes, storms, floods, storm surges and volcanic eruptions. These bring about the loss of lives, property and employment, and damage to the physical infrastructure and the environment. The poor are generally the most vulnerable to the impact of natural disasters, and it is the women and children among them who are often the hardest hit. These impacts are likely to be amplified by a country's particular development patterns, with the level of vulnerability of social groups influenced by the socio-economic patterns and conditions existing prior to the natural disaster. These same patterns and conditions affect survival and recovery of the population following the event. Response to natural disasters in the Caribbean has seen an overemphasis on the replacement of damaged infrastructure at the expense of a closer focus on social aspects of the populations affected. Incorporation of gender analysis into the evaluations carried out in the emergency phase of the disaster cycle can help redress this imbalance to ensure that the differentiated needs of women and men are taken on board during rehabilitation and reconstruction. This document presents tools and methodologies to conduct gender analysis in this area, including: o analysis of the socio-economic effects of natural disasters in the Caribbean from a gender perspective; o a methodological framework for gender analysis.Among the analytical tools presented in this document are: o gender analysis of data collection methods; o evaluation of pre-disaster gender relations; o incorporation of gender analysis in the evaluation of post-disaster casualties and material loss; o examination of the gender aspects underlying the division of labour and allocation of resources; o gender analysis of the impacts on health and social network response. These strategies can help advance gender equality in the Caribbean during the rehabilitation and reconstruction processes that follow in the wake of natural disasters.